Analysis of The Strategy for Collection of Cash Waqf Funds at Baiturrahim Mosque, Lubuk Landai Village, Bungo Regency (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
This study aims to determine how the management of cash waqf at Baiturrahim Mosque, Lubuk Landai Village, Bungo Regency, from the aspect of management strategy and the constraints faced. This study used a qualitative approach with data collection through interview and observation techniques, then presented descriptively. This study found that the management of waqf funds at the Baiturrahim Mosque in Lubuk Landai Village is good from a management perspective, but so far the management orientation is still limited to materials for mosque construction, not yet reaching poverty alleviation, health, education, and other social agendas using this approach. productive waqf. This finding also shows that good waqf management in terms of management still needs to be increased in terms of productivity so that waqf can really overcome social problems faced by Muslims.